MILITARISM AND FEAR IN A TIME OF PANDEMIC IN THE PHILIPPINES: TOWARDS A THEOLOGY OF TRANSGRESSION - K.C. Meneses (Acta Theologica)
The pandemic was an opportunity for authoritarian regimes to intensify militarism and cultivate fear, resulting in the disablement of the most vulnerable in society. Fear dissipates when basic freedoms are at stake. People who once were afraid have learned to transgress, “to step across”, because they just had enough of the Duterte regime’s deception. In light of this context, I argue, like Michel Foucault, that transgression can be a positive notion and not opposed to transcendence. In fact, it belongs to  similar semantic cluster. An interruption can be viewed not as seeking attention, but rather as a cessation that aims for communion. Drawing from the lived experiences of persons with disabilities, I suggest a reversal of the negative perception of interruption to be incarnational, which can pave the way to a theology of transgression that is liberative.